Help seeking behavior and predictors of patient delay after symptom appraisal for oral cancer and perceived barriers. Issue 4 (July 2016) - Agrawal, Mamta; Pandey, Sushma; Jain, Shikha; Gupta, Tulika; Sheoran, Jyoti; Khan, Tayyeb Sultan
Abstract: Objective: The aim of this study was to assess the help seeking behavior and factors predictive of delayed approach to health care professional after symptom appraisal for oral cancer. It also intended to determine the barriers which might contribute to delayed presentation of symptomatic subjects to the clinician. Method: A total of 1635 persons participated in the study. Respondents recording symptom appraisal (226) were then further questioned about their help seeking behavior and barriers to help seeking. Logistic regression analysis was applied to estimate odds ratio (OR) and 95% confidence interval (CI) for delay or no delay in seeking help. Results: An overall delay in the help seeking behavior was observed; 65.5% of the total participants were likely to delay help seeking after symptom appraisal. A significant difference in help seeking behavior was seen among individuals with more symptom knowledge having a mean score of 1.41 (SD = 0.49) in comparison to those having lesser knowledge (mean = 1.29 ± 0.45). Logistic regression analysis revealed 'knowledge of symptoms for oral cancer' as the only significant independent predictor of delay, contributing alone to 17% ( R 2 = 0.17) of the variance in predicting delay. Additionally among the different barriers, indifference toward their symptoms was the most important factor (54.43%) for delay in help seeking. Conclusion: The results of this study show that increased symptom knowledge for oral cancer may decrease patient delay after symptoms appraisal. Recognizing barriers for delayed presentation of the symptomatic subjects to the clinician should be an important aim for improving oral cancer prognosis.